2017
DOI: 10.1037/hea0000450
|View full text |Cite
|
Sign up to set email alerts
|

The link between discrimination and telomere length in African American adults.

Abstract: Results suggest that discrimination experiences accelerate biological aging in older African American males and females, alike. This finding helps advance our understanding of how discrimination generates greater disease vulnerability and premature death in African Americans. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 81 publications
5
46
0
Order By: Relevance
“…The current findings extend the applications of extant stress theories (Clark, Anderson, Clark, & Williams, 1999; Paradies, 2006) and complement previous work showing inverse links between discrimination and specifically, racial discrimination and telomere length (Chae et al, 2014, 2016; Lee et al, 2017; Liu & Kawachi, 2017). They also expand upon prior reports in several ways.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current findings extend the applications of extant stress theories (Clark, Anderson, Clark, & Williams, 1999; Paradies, 2006) and complement previous work showing inverse links between discrimination and specifically, racial discrimination and telomere length (Chae et al, 2014, 2016; Lee et al, 2017; Liu & Kawachi, 2017). They also expand upon prior reports in several ways.…”
Section: Discussionsupporting
confidence: 87%
“…Department of Health and Human Services (2014), highlight the need for research on social statuses and discrimination to further elucidate health disparities. A prior report on discrimination and telomere length (Lee et al, 2017) observed that neither age nor sex moderated the associations between major life discrimination and telomere length in older African Americans. Perhaps concurrently considering age and sex alongside other social statuses may reveal different effects.…”
Section: Introductionmentioning
confidence: 83%
“…Racial discrimination is also associated with shorter telomere length, which is a marker of aging (27). Racial discrimination is associated with higher levels of nervousness and anger and higher likelihood of evaluating social interactions as harassing (28).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also recently found associations between TL and discrimination (Chae et al, , ;Lee et al, ; Liu & Kawachi, ). Two of these studies only reported significant findings after they added discrimination in a statistical interaction with either depressive symptoms (Chae et al, ) or an internalized anti‐black racial bias (Chae et al, ).…”
Section: Discussionmentioning
confidence: 80%
“…Researchers have previously investigated the impact of discrimination stress on TL in African Americans. For example, the Health and Retirement Study (HRS) recently found that everyday discrimination (per the Everyday Discrimination Scale‐Short Form; EDS‐SF; Sternthal & Williams, ) was associated with shorter telomeres in African American adults (Lee, Kim, & Neblett, ; Liu & Kawachi, ). The same association was not observed among European Americans enrolled in the HRS (Liu & Kawachi, ).…”
Section: Introductionmentioning
confidence: 99%